2020
DOI: 10.3389/fphar.2020.01193
|View full text |Cite
|
Sign up to set email alerts
|

Basic Fibroblast Growth Factor Attenuates Injury in Myocardial Infarction by Enhancing Hypoxia-Inducible Factor-1 Alpha Accumulation

Abstract: Background: The combination of antiapoptotic and angiogenic actions may represent a pharmacotherapeutic strategy for the treatment of myocardial infarction. Fibroblast growth factor (FGF) is expressed in various cell types including endothelial and muscle cells and promotes their survival, migration, and proliferation. Methods and Results: Myocardial microvascular endothelial cells were divided into four treatment groups, the sham, hypoxia, basic FGF (bFGF), and bFGF plus 2methoxyestradiol groups, and subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
(31 reference statements)
2
10
0
Order By: Relevance
“…It is not clear from our results alone how encapsulated MSCs promote the secretion of growth hormones. However, several studies have suggested that HIF‐1α promotes the secretion of growth hormones such as VEGF and FGF 30,31 . We also confirmed that hypoxic conditions occurred in the encapsulated MSCs (Fig.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It is not clear from our results alone how encapsulated MSCs promote the secretion of growth hormones. However, several studies have suggested that HIF‐1α promotes the secretion of growth hormones such as VEGF and FGF 30,31 . We also confirmed that hypoxic conditions occurred in the encapsulated MSCs (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…However, several studies have suggested that HIF-1α promotes the secretion of growth hormones such as VEGF and FGF. 30,31 We also confirmed that hypoxic conditions occurred in the encapsulated MSCs (Fig. 6c) and that growth hormone levels were higher in encapsulated MSCs than in monolayer culture conditions.…”
Section: Discussionsupporting
confidence: 75%
“…Positive modulatory effects of FGF1 and FGF2 in the repair of induced ischemia-reperfusion injury and MI were revealed to be based on cardiomyocyte proliferation, stimulation of angiogenesis and the recovery of MI-induced remodeling, systolic and diastolic activities of the heart ( Engel et al, 2006 ; Formiga et al, 2014 ; Garbayo et al, 2016 ; Rao et al, 2020 ). This repairing function of FGF1 is further improved by co-treatment of FGF1 with an inhibitor of p38 MAPK.…”
Section: Roles Of Fgf In Cardiac Pathophysiology and Repairmentioning
confidence: 99%
“…The action of Fgfr2 overexpression together with the reduction in cardiomyocyte apoptosis after MI is correlated to upregulation of Fgf2 and its autocrine effect ( Matsunaga et al, 2009 ). Anti-apoptotic and pro-angiogenic protective responses following FGF2 treatment after MI in mice were induced through activation of the AKT-hypoxia-inducible factor-1 alpha (HIF-1α)-VEGF axis ( Rao et al, 2020 ). In cardiac regeneration of the zebrafish after injury, the active presence of the FGF-AKT signaling cascade is required for the survival of cardiomyocytes ( Tahara et al, 2021 ).…”
Section: Roles Of Fgf In Cardiac Pathophysiology and Repairmentioning
confidence: 99%
“…Heart was exposed in the fourth and fifth intercostal gap after left thoracotomy, when left anterior descending coronary artery (LAD) running in myocardial tissues consistent with the direction of the great myocardial vein was found, it was sutured and ligated with 6-0 silk thread. After LAD occlusion, the corresponding blood supply area was whitened, while infarction manifestations such as ST segment elevation was noticed as electrocardiogram displayed ( 11 , 18 , 20 - 23 ). Subsequent treatments were performed 30 min after ligation ( 22 ).…”
Section: Methodsmentioning
confidence: 99%